Mixed Convective Heat Transfer Phenomena of Circular Cylinders to Non-Newtonian Nanofluids Flowing Upward. (2015) - Singh, Abhipsit Kumar; Harinadha, G.; Kishore, Nanda; Barua, Purnima; Jain, Tarash; Joshi, Priyamvada
Abstract: A numerical investigation on mixed convection heat transfer has been carried out from an isothermal unconfined circular cylinder to a power-law type non-Newtonian nanofluid which is flowing vertically upward past the cylinder. The effect of buoyancy is same as the direction of flow (i.e. vertical upward flow). The temperature of circular cylinder is higher than that of surrounding nanofluid. The continuity, momentum and energy equations are simultaneously solved numerically within the limitation of Boussinesq approximation using a commercial computational fluid dynamics based solver FLUENT 6.3.26. The semi implicit method for pressure-linked equations (SIMPLE) scheme is used to solve the problem of velocity-pressure coupling. The range of parameters considered for this study is as following: volume fraction of nanoparticles (0.005 ≤ Φ ≤ 0.045), Reynolds number (1 ≤ Re ≤ 40), and Richardson number (0 ≤ Ri ≤ 5). The corresponding values of the power-law behavior ( n ) and power-law consistency ( m ) indices of nanofluids of volume fractions 0.005, 0.0015, 0.0025, 0.0035, 0.0045 are n = 0.88, 0.78, 0.68, 0.58, 0.50, and m = 0.00187, 0.00283, 0.00426, 0.00641, 0.00876, respectively. The convergence criteria are fixed to 10 -8 for continuity and momentum equation and 10 -10 for energy equation. For the above mentioned parameters, the heat transfer characteristics like isotherm contours, and average Nusselt numbers have been given quantitatively. The effect of Richardson number ( Ri ), volume fraction of nanoparticles ( Φ ) and Reynolds number ( Re ) on the global characteristics have been explained. It also verifies that as Richardson number increases at specific Reynolds number, the average Nusselt number increases.